Coexistence in Times of Climate Crisis: A Participatory Mapping to Understanding Conservation Conflicts in the Central Andes of Chile - Vargas, Solange P.; Hargreaves, Matías; Del Valle, Juan Pablo; Hodges, Aline; Beltrami, Esperanza; Toledo, M. F.; Sapaj-Aguilera, Guillermo (Frontiers in Conservation Science, 2022)
Purpose Human-wildlife conflicts worldwide are arising, representing significant challenges for conservation biologists, decision-makers, and agropastoralist communities. Extreme climatic events, disease outbreaks, and land-use change could be intensifying these conflicts. The multi-species and mountainous landscapes seem prone to conflicts due to a lack of territory planning. These complex, dynamic, and multi-layered conflicts require a multidimensional approach. Currently, in Chile, mountainous landscapes have several threats, such as a lack of territory planning, mega-mining projects, and recently (last 10 years) the effects of the Mega-drought. Many transhumant agropastoralists have been forced to quit their livelihoods while increasing livestock-wildlife conflicts. We aim to build territorial planning within a holistic approach to strengthening the agropastoralists' competence to coexist with local wildlife (puma, condor, and guanaco) in Central Chile's Andes mountains. Methodology We conducted participatory mapping workshops with two agropastoralist communities in 2020. They were randomly divided into 4 to 7 people groups and told to draw a map representing their territory, including four elements: (1) natural and human components of the landscape, (2) natural wildlife conflict areas, (3) active grazing areas, and (4) their ideal future scenario, regarding their activity. Findings Results showed different spatial perceptions of the natural and human components of the territory. All agropastoralists (100%) indicated similar wildlife conflict areas: focusing in the Summerlands. All agreed that Mega-drought was the primary threat to their production, increasing the conflict with wildlife. Summerland areas are identified as suitable areas for working in conflict with wildlife. Research Limitations/Implications This study highlights the need for a multidimensional approach to conflict and territory planning to address conservation conflicts. The study's implications show that agropastoralists decided to reduce Summerland use and improve Winterland planning to increase livestock productivity and reduce conflict with wildlife. Participatory mapping could help to prioritize areas to mitigate conflicts with wildlife. Originality/Value This study is the first in the Aconcagua valley to conduct a transdisciplinary & participatory approach toward coexistence between transhumant agropastoralists and wildlife. It also provides a baseline for similar schemes in semi-arid and mountainous landscapes worldwide facing rapid climate shifts and increasing human-wildlife conflict.